Mathematical methods for forecasting the company's financial results - Urbonaitė, Judita; Kvekšienė, Milda (Buhalterinės apskaitos teorija ir praktika, 2013)
Forecasting is essential for the company activities, as it helps to predict company's future results. Forecasting methods theory analysis has showed that the application of mathematical methods are very wide. After the forecasting of sales revenue and profits of „Klaipėda vanduo“ LC. for 2013–2014 has been done, it is possible to claim that forecasting according to parabolic trend is appropriate for forecasting indicators, one the grounds that MAPE index for sales revenue and gross profit indicators has turned out to be very accurate, and for financial forecast - accurate. Linear trend forecasting is also suitable for the sales revenues forecasting due to the similarity of received calculated errors. The results achieved have depicted that according to the linear trend the sales revenues average will be 41,48 million litas in 2013. The average of the sales revenues according to parabolic trend will be 41,56 million litas. In 2014 according to linear trend the sales revenues will reach 41,70 million litas and according to parabolic trend they will reach 41,87 million litas. Gross profit in 2013 is forecasted to be 8,21 million litas and in 2014 – 5,4 million litas. 2013 and 2014 forecasting showed, that company will suffer net losses.
Keywords: exponential smoothing; extrapolation; correlation; regression; trend